1998
DOI: 10.1128/aac.42.7.1629
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of a Selective Ribonucleotide Reductase Inhibitor against Acyclovir-Resistant Herpes Simplex Virus Type 1 In Vivo

Abstract: The present study reports the activity of BILD 1633 SE against acyclovir (ACV)-resistant herpes simplex virus (HSV) infections in athymic nude (nu/nu) mice. BILD 1633 SE is a novel peptidomimetic inhibitor of HSV ribonucleotide reductase (RR). In vitro, it is more potent than ACV against several strains of wild-type as well as ACV-resistant HSV mutants. Its in vivo activity was tested against cutaneous viral infections in athymic nude mice infected with the ACV-resistant isolates HSV type 1 (HSV-1) dlsptk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…In vitro studies have shown that inhibitors of cellular RR or the HSV-1 or VZV RRs (including HU, FMdC, A723U, A1110U, BW348U87, and the “BILD” series of peptidomimetics) exhibit antiviral activity when used alone and either potentiate or result in synergy when used in combination with ACV against wild type or drug-resistant strains of VZV, HSV-1, or HSV-2 (Bridges et al, 1995; Duan et al, 1998; Ellis et al, 1989; Lawetz and Liuzzi, 1998; Liuzzi et al, 1994; Moss et al, 1996, 1995; Neyts and De Clercq, 1999; Prichard and Shipman, 1995; Sergerie and Boivin, 2008; Spector et al, 1985, 1987, 1989). HU has also been shown to potentiate the activity of cidofovir and to synergize with GCV to inhibit replication of wild type or drug-resistant strains of HSV-1 or HSV-2 (Neyts and De Clercq, 1999; Sergerie and Boivin, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown that inhibitors of cellular RR or the HSV-1 or VZV RRs (including HU, FMdC, A723U, A1110U, BW348U87, and the “BILD” series of peptidomimetics) exhibit antiviral activity when used alone and either potentiate or result in synergy when used in combination with ACV against wild type or drug-resistant strains of VZV, HSV-1, or HSV-2 (Bridges et al, 1995; Duan et al, 1998; Ellis et al, 1989; Lawetz and Liuzzi, 1998; Liuzzi et al, 1994; Moss et al, 1996, 1995; Neyts and De Clercq, 1999; Prichard and Shipman, 1995; Sergerie and Boivin, 2008; Spector et al, 1985, 1987, 1989). HU has also been shown to potentiate the activity of cidofovir and to synergize with GCV to inhibit replication of wild type or drug-resistant strains of HSV-1 or HSV-2 (Neyts and De Clercq, 1999; Sergerie and Boivin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In murine models of HSV-1- or HSV-2-induced cutaneous or ocular lesions, RR inhibitors administered topically showed therapeutic efficacy and exhibited potentiation or synergy when used in combination with ACV (Brandt et al, 1996; Bridges et al, 1995; Duan et al, 1998; Ellis et al, 1989; Liuzzi et al, 1994; Lobe et al, 1991; Moss et al, 1995, 1996; Spector et al, 1992). Combination therapies were also effective for treating lesions caused by ACV-resistant strains (Duan et al, 1998; Ellis et al, 1989; Lobe et al, 1991; Spector et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The peptidomimetic drugs prevent the formation of an active RR by competitively inhibiting the binding of R2 to R1 [313][314][315][316][317]. The difference between the C terminus sequence of R2 of different species is important to develop highly specific inhibitors that can inhibit a parasite RR without interfering with the host RR [313,314,318,319]. A herpes simplex virus (HSV) RR inhibitor, BILD 1633 SE has shown activity against cutaneous acyclovir-resistant HSV-1 infections in an athymic nude mouse model.…”
Section: Polymerization Inhibitionmentioning
confidence: 99%
“…These inhibitors are based on the C-terminal amino acid sequence of the HSV RR small subunit (R2), VVNDL, which bind to the RR large subunit (R1) and permits subunit association and subsequent catalytic activity. The inhibitors, which mimic this C-terminal sequence, but are modified to enhance stability, competing with R2 for binding to R1, show antiviral activity in vivo, suppress the replication of HSV-1, HSV-2 and acyclovir-resistant HSV strains in cell culture, and also strongly potentiate the antiviral activity of acyclovir [56][57][58][59].…”
Section: Peptides As Inhibitors Of Protein-protein Interactionsmentioning
confidence: 98%